Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to find the sum of the infinite series

$$\frac{1}{12}-\frac{1\cdot 4}{12 \cdot 18 } + \frac{1\cdot 4\cdot 7}{12\cdot 18\cdot 24} - \frac{1 \cdot 4 \cdot 7\cdot 10}{12 \cdot 18 \cdot 24 \cdot 30}+...$$

I understood the answer posted in Yahoo Answer till the last but one step:

That is how did he get: $ \lim_{n \to \infty} S_n = 0 $

Other steps I understood.

Thanks in advance

share|cite|improve this question
What methods have you learned for summing series? Why "DESPERATE"? – Jonas Meyer Jan 17 '13 at 17:33
I know only the limits technique. Is this correct? I asked in Yahoo answers and [link][/… and got the answer but I did not get how he got lim n--> inf s[n] as 0. – user58648 Jan 17 '13 at 17:34
It is related to the binomial series for $\left(1+\dfrac12\right)^{2/3}$. – Jonas Meyer Jan 17 '13 at 18:01
@user58648: Glipp's answer is wrong. The recursive formula for the coefficients is confused with a (wrong) recursive formula for the partial sums. – Jonas Meyer Jan 17 '13 at 18:05
@experimentX, $\Gamma(1/3)/\Gamma(4/3) = 3$. – Antonio Vargas Jan 17 '13 at 18:12

We can rewrite the series as $$ \begin{align} -3\sum_{n=2}^\infty\binom{2/3}{n}(1/2)^n &=-3\left((1+1/2)^{2/3}-1-1/3\right)\\ &=4-3\ (3/2)^{2/3} \end{align} $$

A Bit of Explanation

By the Generalized Binomial Theorem, we have $$ \sum_{n=0}^\infty\binom{2/3}{n}(1/2)^n=(1+1/2)^{2/3} $$ The first two terms are $\binom{2/3}{0}(1/2)^0=1$ and $\binom{2/3}{1}(1/2)^1=1/3$. Subtracting the first two terms yields $$ \sum_{n=2}^\infty\binom{2/3}{n}(1/2)^n=(1+1/2)^{2/3}-1-1/3 $$

The General Term $$ \begin{align} \binom{2/3}{n}(1/2)^n &=\frac{2/3(-1/3)(-4/3)\dots(5/3-n)}{1\cdot2\cdot3\cdots n}\frac1{2^n}\\ &=\frac{2(-1)(-4)(-7)\dots(5-3n)}{6\cdot12\cdot18\cdot24\cdots(6n)} \end{align} $$ which is $-1/3$ of the general term of the series.

share|cite|improve this answer
how did you write the series like that? could you add a bit more explanation? – Santosh Linkha Jan 17 '13 at 19:03

Using the fact that

$$ \prod_{k=0}^{n}(12+6k) = 6^{n+1}(n+2)! = 3^{n+1} 2^{n+2} \frac{(n+2)!}{2} $$

we see that the $n^{\text{th}}$ term is

$$ \begin{align*} (-1)^n \frac{\prod_{k=0}^{n}(1+3k)}{\prod_{k=0}^{n}(12+6k)} &= \frac{\prod_{k=0}^{n}\left(\frac{1}{3}-k\right)}{\frac{(n+2)!}{2}} \cdot \frac{1}{2^{n+2}} \\ &= \frac{3}{(n+2)!} \cdot \frac{2}{3} \prod_{k=0}^{n}\left(\frac{1}{3}-k\right) \cdot \frac{1}{2^{n+2}} \\ &= -\frac{3}{(n+2)!} \cdot \prod_{k=0}^{n+1}\left(\frac{2}{3}-k\right) \cdot \frac{1}{2^{n+2}} \\ &= -3 \cdot \binom{2/3}{n+2} \cdot \frac{1}{2^{n+2}}. \end{align*} $$

Hence the value of the sum is

$$ \begin{align*} -3 \sum_{n=2}^{\infty} \binom{2/3}{n} \cdot \frac{1}{2^n} &= 4-3-3\frac{2}{3}\cdot\frac{1}{2}-3 \sum_{n=2}^{\infty} \binom{2/3}{n} \cdot \frac{1}{2^n} \\ &= 4 - 3 \sum_{n=0}^{\infty} \binom{2/3}{n} \cdot \frac{1}{2^n} \\ &= 4 - 3 \left(1+\frac{1}{2}\right)^{2/3}. \end{align*} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.